2018
DOI: 10.1371/journal.pone.0197109
|View full text |Cite
|
Sign up to set email alerts
|

HBV subgenotypes F1b and F4 replication induces an incomplete autophagic process in hepatocytes: Role of BCP and preCore mutations

Abstract: Hepatitis B virus (HBV) genotypes and mutants have been associated with differences in clinical and virological characteristics. Autophagy is a cellular process that degrades long-lived proteins and damaged organelles. Viruses have evolved mechanisms to alter this process to survive in host cells. In this work, we studied the modulation of autophagy by the replication of HBV subgenotypes F1b and F4, and the naturally occurring mutants BCP and preCore. HBV subgenotypes F1b and F4 replication induced accumulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…For instance, newly emerged research indicated that SARS‐CoV‐2 induced incomplete autophagy in infected cells and increased the replication efficiency of SARS‐CoV‐2 8 . Similarly, other reports investigated that coxsackievirus A16, PRRSV, Epstein–Barr virus, Porcine tescho virus 2, and HBV infection‐induced incomplete autophagy resulting in increased the virus replication and production 75,127,156–158 . Besides, incomplete autophagy is related to pro‐inflammatory microglia activation following infection of Japanese encephalitis virus 159 .…”
Section: Implications Of Incomplete Autophagy For Pharmacotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, newly emerged research indicated that SARS‐CoV‐2 induced incomplete autophagy in infected cells and increased the replication efficiency of SARS‐CoV‐2 8 . Similarly, other reports investigated that coxsackievirus A16, PRRSV, Epstein–Barr virus, Porcine tescho virus 2, and HBV infection‐induced incomplete autophagy resulting in increased the virus replication and production 75,127,156–158 . Besides, incomplete autophagy is related to pro‐inflammatory microglia activation following infection of Japanese encephalitis virus 159 .…”
Section: Implications Of Incomplete Autophagy For Pharmacotherapymentioning
confidence: 99%
“…8 Similarly, other reports investigated that coxsackievirus A16, PRRSV, Epstein-Barr virus, Porcine tescho virus 2, and HBV infection-induced incomplete autophagy resulting in increased the virus replication and production. 75,127,[156][157][158] Besides, incomplete autophagy is related to pro-inflammatory microglia activation following infection of Japanese encephalitis virus. 159 Therefore, inhibition of incomplete autophagy can effectively inhibit viruses, which is a promising strategy for the development of novel antiviral drugs.…”
Section: Infectious Diseasesmentioning
confidence: 99%
“…Transfected cells were lysed in 1X Laemmli buffer, boiled, loaded on 12% sodium dodecyl sulfate (SDS)-polyacrylamide gels, and transferred to polyvinylidene fluoride membranes (Hybond), according to standard protocols. 20 HBc was detected with HBc-170A polyclonal antibody (kindly provided by Dr. Ju-Tao Guo). β-Actin detection was used as intracellular protein loading control.…”
Section: Western Blotmentioning
confidence: 99%